Incidence of Intussusception in Bamako, Mali, Before and After the Introduction of Rotavirus Vaccine. Issue 9 (17th June 2022) - Roose, Anna; Keita, Adama Mamby; Tapia, Milagritos D; Sow, Samba O; Mast, T Christopher; Kotloff, Karen L
Abstract: Pentavalent rotavirus vaccine has been associated with a small increase in intussusception, but pre- and post-introduction data are lacking in many low-resource settings. Using chart review and prospective surveillance data, intussusception incidence was estimated in Bamako, Mali. The mean annual intussusception incidence post-introduction was not significantly different from that of pre-introduction. Abstract : The association between rotavirus vaccines and intussusception has raised concern about the risk-benefit ratio of these vaccines in low-resource settings. We describe rates of intussusception among infants in Bamako, Mali, before and after the introduction of pentavalent rotavirus vaccine.